Virtual collaboration for a distributed enterprise - Cordova, Amado; Keller, Kirsten M.; Menthe, Lance; Rhodes, Carl, 1970- (RAND, 2013)
The geographic diversity of many military enterprises, along with that of their partners and customers, has made virtual collaboration indispensable for conducting daily operations. Virtual collaboration tools can enable intrasite and intersite collaborative analyses, allow for sites to provide more effective surge capacity, and allow the regional expertise developed at each site to be applied wherever necessary across the enterprise. But communication between non-colocated (virtual) teams poses important challenges, including potential difficulty building cohesiveness and trust among team members and difficulty establishing a common understanding of information or situations. This report addresses these challenges through an assessment of three modes of virtual collaboration, computer-mediated communication, audioconferencing, and videoconferencing, and recommends several ways for intelligence enterprises to tackle them using virtual collaboration tools. These recommendations include: (1) determine which virtual collaboration tools and features are most beneficial using experimental research involving simulated tasks and constraints that closely mirror the military enterprise's operational environment; (2) standardize the lexicon and communications practices associated with virtual collaboration-chat, in particular-and train personnel in these practices; and (3) explore the use of videoconferencing in real-time communications between personnel, their partners, and their customers at different sites. In particular, we recommend that Air Force intelligence enterprises consider the use of personal or webcam-based videoconferencing between intelligence personnel located at different sites, as well as between these personnel and remotely piloted aircraft flight crews.